Storyboard That- Based Digital Comics In Grade V Elementary School Students - Dwi Cahaya Nurani; Vina Amilia Suganda M; budiansyah budiansyah; Dewinta Aulia Savitri; Fahmi Surya Adikara (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2024)
The development of digital comics based on Storyboard aims to enhance the understanding of fifth-grade elementary school students in the subject of Social Studies, particularly the topic of the arrival of European nations in Indonesia, within a thematic learning context. The goal is to ensure that the learning process is effective and aligns with the intended learning outcomes. The digital comic based on Storyboard contains a sequence of materials accompanied by supporting images to visualize the historical events, making it engaging for students to learn. The use of digital comics based on Storyboard as a teaching tool is expected to assist teachers in improving the quality of the history teaching process, making it easier for students to comprehend the subject matter. The research methodology employed in this study is Research and Development (R&D). The results of the research indicate that the development of digital comics based on Storyboard That is suitable for independent student learning, as evidenced by the effectiveness test, which yielded a value of 0.82, falling into the "high" category. This suggests that digital comics based on Storyboard That have a significant impact and are effective in enhancing Social Studies learning, particularly in history, within the thematic learning context for fifth-grade elementary school students